Renal Physiology and Hydrosaline Metabolism - Gallardo, Pedro A.; Vio, Carlos P. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This volume discusses renal function and the mechanisms by which the kidney regulates the composition and volume of the extracellular fluid. It also highlights the role of the kidney in the development and progression of arterial hypertension. Most textbooks of renal physiology are based in mammalians physiology and mostly human physiology of the kidney, but the authors considered that this book should also include other species to include the broad spectrum of students and researchers in the life and biomedical sciences. In this sense, we included chapters such as comparative osmoregulation in non-mammalian vertebrates and we emphasize that in vertebrates like fish, reptiles, amphibians and birds, the kidneys and extrarenal organs are vital to maintain fluid homeostasis. The purpose of the book is to provide a concise frame of knowledge in a clear and direct language, of the renal function to medical and biological sciences students. In the context of normal renal function, we provide pathophysiological basis for chronic renal diseases and hypertension with the participation of renal vasoactive hormones. This book is used as textbook in several physiology courses for medical, nursing and biological sciences students at the Pontifical Catholic University of Chile, Finis Terrae University, Universidad San Sebastian as well as other universities. This book is a translation of an original Spanish edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
1.General functions of the kidney -- 2.Functional Anatomy of the Kidney -- 3.Glomerular Filtration and Renal Blood Flow -- 4.Transport of NaCl, organic solutes and water in the renal tubule -- 5.Water Balance and the Regulation of Plasma Osmolality -- 6.Osmoregulation in Non-Mammalian Vertebrates -- 7.Regulation of the Effective Circulating Volume and Sodium Balance -- 8.Renal Regulation of Acid-Base Balance -- 9.Potassium Balance Regulation -- 10.Tubular Transport of Calcium, Phosphate and Magnesium -- 11.Kidney hormones and their actions -- 12.Pathophysiological basis of high blood pressure -- 13.Genetic Alterations in Tubular Transportation of NaCl And Water -- 14.Answers to review questions.
Keywords: Human physiology; Physiology; Internal medicine; Urology; Human Physiology; Animal Physiology; Internal Medicine; Urology